Inhibitory effects of rice residues amendment on Cd phytoavailability: A matter of Cd-organic matter interactions?. (November 2017) - Tang, Wenli; Zhong, Huan; Xiao, Lin; Tan, Qiaoguo; Zeng, Qilong; Wei, Zhongbo
Abstract: Incorporating crop residues into soils, a most common way of organic input into farmland soils, is being encouraged in many parts of the world, while its potential impacts on Cd phytoavailability are not well understood. Here, a Cd-contaminated soil was amended with rice residues (RR, i.e., straw + root mixture) or not (Control) and incubated for 81 days under laboratory-controlled conditions. During the incubation, key soil parameters (e.g., dissolved organic carbon and pH), Cd geochemical fractionation (by BCR sequential extraction), and CaCl2 extracted Cd in soils (by 0.01 M CaCl2 extraction) were quantified to explain the effects of RR amendment on Cd phytoavailability (assessed by 7 day-cultivation of rice seedling in soils). Besides, hydroponic experiments were designed to explore the effects of D-RR-OM (dissolved-RR-organic matter) on the uptake of Cd by rice seedlings (quantified by uptake constant rate, k u, using stable isotope tracing technique). Our results demonstrated that RR amendment reduced Cd phytoavailability by 17–92% compared with Control during incubation, which might be explained by the interactions between Cd and RR-OM (RR-organic matter) in soil or porewater: (1) Cd immobilization due to its association with solid-RR-OM in soils, (2) Cd mobilization by D-RR-OM, and (3) Cd complexation with D-RR-OM in porewater, and thus reduced k u of Cd. Our results suggested that dynamics of RR-OM (e.g., dissolution, decomposition and transformation) in soils, and thus interactions between Cd and solid/dissolved-RR-OM may control Cd phytoavailability under RR amendment. Information gained in this study would further our understanding about Cd phytoavailability in farming soils. Highlights: Rice residues (RR) amendment reduced Cd phytoavailability in soils. Cd association with solid-RR-OM (solid-RR-organic matter) resulted in immobilization of Cd in soils. D-RR-OM (dissolved-RR-organic matter), due to dissolution/decomposition of RR-OM (RR-organic matter), mobilized Cd in soils. Cd complexation with D-RR-OM reduced Cd availability to rice seedlings.